Fuel Planning Analysisng of Extended Twin Engine Operations for Jakarta - Jeddah Route - Alfaridzi, Alfian Yannu; Indriyanto , Toto (Langit Biru: Jurnal Ilmiah Aviasi, 2024)
This study analyzes ETOPS fuel planning for an Airbus A330-343 from Jakarta (CGK) to Jeddah (JED) route, comparing 90-minute and 120-minute diversion times across four flight cases: standard, pressure loss, engine failure, and combined pressure loss with engine failure. Industry-standard methodologies were employed to calculate fuel requirements, payload capacities, and flight durations for each scenario. Results indicate that the 120-minute diversion time generally offers advantages in fuel efficiency and payload capacity. The standard fuel plan for 120-minute diversion required 63,790 kg of fuel, compared to 64,689 kg for the 90-minute scenario. Pressure loss cases demanded the highest fuel consumption in both scenarios. The 120-minute diversion time also allowed for a more direct flight path, reducing overall flight duration in most cases. This research provides insights into optimizing ETOPS fuel planning for long-haul twin-engine aircraft operations, potentially enhancing operational efficiency and economic performance while maintaining safety standards in commercial aviation